2023
DOI: 10.3390/foods12061122
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Response of Stored Pomegranate Fruit Affected by Simulated Impact

Abstract: Mechanical damage resulting from excessive impact force during handling and other postharvest operations from harvesting to consumption is a critical quality problem in fresh produce marketing. The study investigates the impact of bruise damage, storage temperature, and storage period on the physiological responses of Omani pomegranate fruit cultivar ‘Helow’. Fruits were subjected to low (45°; 1.18 J) and high (65°; 2.29 J) impact levels using a pendulum test by hitting the fruit on the cheek side. Bruised and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 35 publications
(59 reference statements)
0
4
0
Order By: Relevance
“…Fresh cucumber weight loss is mostly due to water loss produced by transpiration and respiration processes [11]. Pathare et al [24] showed that weight loss % was strongly impacted by the storage temperature, impact heights, and storage duration, particularly at ambient temperature.…”
Section: Weight Loss (Wl%)mentioning
confidence: 99%
See 1 more Smart Citation
“…Fresh cucumber weight loss is mostly due to water loss produced by transpiration and respiration processes [11]. Pathare et al [24] showed that weight loss % was strongly impacted by the storage temperature, impact heights, and storage duration, particularly at ambient temperature.…”
Section: Weight Loss (Wl%)mentioning
confidence: 99%
“…According to Bodner and Scampicchio[27],bruising is one of the factors that causes fruit discoloration. The observed changes in color characteristics could be attributed to the rapid chlorophyll breakdown during the storage of bruise-damaged cucumbers[24].…”
mentioning
confidence: 96%
“…As a result, the delivery quality of fruits cannot meet the industrial requirements. The weight-loss ratio is an index used to evaluate the freshness basis of fruits, and it is the most intuitive index for determining changes in fruit quality [7] . It directly influences the shelf life and economic value of fruits.…”
Section: Introductionmentioning
confidence: 99%
“…organic components such as organic acids, proteins, and fats are metabolized (Jung et al, 2019). Therefore, over time, the nutritional content, flavor, color, and other characteristics of fruit will diminish (Ebrahimi et al, 2022;Pathare et al, 2023). Because it takes some time for fruit to go through processing, transportation, and retail, effective methods are needed to extend its duration of freshness (Joung et al, 2021).…”
mentioning
confidence: 99%